Exploring the experiences of health-promoting behavior in the workplace among Thai pregnant women: A phenomenological approach - Sasitara Nuampa; Pornnapa Tangsuksan; Crystal L Patil (Wolters Kluwer Medknow Publications, 2023)
Background: Inappropriate working conditions during pregnancy can negatively affect health-promoting behaviors and pregnancy outcomes. This study aimed to explore the experiences of health-promoting behavior in the workplace among Thai pregnant women. Materials and Methods: Giorgi's phenomenological methodology was used, and data were gathered through semi-structured interviews with 21 working-pregnant women in large industries in two regions of Thailand. Data were collected from December 2019 to June 2020. Purposive and snowball sampling were used to recruit pregnant women at 13-42 weeks of gestation. To analyze the data, three steps of Giorgi's phenomenological approach were employed. Results: The pregnant women described their lived experiences with health-promoting behaviors in the workplace into four major categories. Firstly, "positive attitude toward work in promoting health behaviors" contained three subcategories ("self-discipline," "social interaction," and "self-esteem"). Secondly, the idea that "changing temporary health behaviors is worthwhile for infants" was expressed into two subcategories ("eating adaptation" and "managing negative emotions"). Thirdly, "insufficient support from workplace policy" had three subcategories ("inconvenient accommodations," "inflexible break times," and "lack of healthcare support"). Finally, "negative perception of new work positions" consisted of two subcategories ("stress" and "low self-efficacy"). Conclusions: Positive attitudes toward work and infant health may encourage pregnant women to engage in healthy behaviors, while workplace support and policies are important in promoting healthy behavior and avoiding negative emotions. Health promotion interventions should encourage the value of work, promote maternal-fetal attachment, and increase health support policy to avoid mental health issues and promote healthy behaviors among working-pregnant women.